Etiology of Infectious Keratitis as Seen at a Tertiary Care Center in Larkana, Pakistan - Huda Fatima, Ali Akbar Soomro, Syed Imtiaz Ali Shah, Shujaat Ali Shah, Partab Rai Safdar Ali Abbasi (Pakistan Journal of Ophthalmology, 2016)
Purpose: To determine the different causes of infectious keratitis and their relative frequencies in the patients coming to a tertiary care center in Larkana, Pakistan. Study Design: Prospective case series. Place and duration of study: This study was carried out at the Department of Ophthalmology, Chandka Medical College Hospital Larkana, Pakistan, from February 2004 up till February 2015. Material and Methods: The number of patients clinically diagnosed as case of infectious keratitis included in the study, were 2411. Patients excluded from the study were under the age of 16 years, or having Mooren’s ulcer, or ulcers associated with exposure, autoimmune and systemic diseases. Corneal swabs or scrapings were taken and prepared on separate slides for microscopic evaluation of Bacteria, Fungi and Acanthamoeba; while the viral keratitis was diagnosed on clinical grounds. A standard proforma, including sex and age of the patient, clinical diagnosis and the results of corneal scrapings, was filled for each patient. SPSS version 20 was used for data entry and analysis. Results: Out of the total 2411 patients, 60.02% were males and 39.98% were females. The mean age (± standard deviation) was 36.73 ± 15.49 years. The final report showed that the major cause of infectious keratitis were Bacteria with 56.12% of the total cases, followed by Fungi with 38.45%. Cases of Viral keratitis were 3.65% and 1.78% patients had Acanthamoeba keratitis. Conclusion: Bacteria and Fungi are responsible for the bulk (94.57%) of infectious keratitis but Virus and Acanthamoeba should not be ignored or underestimated. Keywords: Keratitis, Acanthamoeba keratitis, Eye Infections, Bacterial, Fungal, Viral.